2014
DOI: 10.1155/2014/916521
|View full text |Cite
|
Sign up to set email alerts
|

Differential Macrophage Response to Slow- and Fast-Growing Pathogenic Mycobacteria

Abstract: Nontuberculous mycobacteria (NTM) have recently been recognized as important species that cause disease even in immunocompetent individuals. The mechanisms that these species use to infect and persist inside macrophages are not well characterised. To gain insight concerning this process we used THP-1 macrophages infected with M. abscessus, M. fortuitum, M. celatum, and M. tuberculosis. Our results showed that slow-growing mycobacteria gained entrance into these cells with more efficiency than fast-growing myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 63 publications
(70 reference statements)
2
27
0
Order By: Relevance
“…Helguera-Repetto et al (2014) compared THP-1 cells infected with M. abscessus, M. fortuitum, M. celatum, and MTB. They found that over a two day period of infection, there was increased growth of M. abscessus and M. fortuitum but the number of M. celatum and MTB remain relatively constant temporally (Helguera-Repetto et al, 2014). The significant differences in the experiments conducted between their study and ours -including differences in MOI used, times of infection before washing the cell culture, maximum time of infection, NTM species used, and macrophage effector function assayed -make these two studies complementary.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Helguera-Repetto et al (2014) compared THP-1 cells infected with M. abscessus, M. fortuitum, M. celatum, and MTB. They found that over a two day period of infection, there was increased growth of M. abscessus and M. fortuitum but the number of M. celatum and MTB remain relatively constant temporally (Helguera-Repetto et al, 2014). The significant differences in the experiments conducted between their study and ours -including differences in MOI used, times of infection before washing the cell culture, maximum time of infection, NTM species used, and macrophage effector function assayed -make these two studies complementary.…”
Section: Discussionmentioning
confidence: 82%
“…Others have also compared various species of NTM with or without comparison to MTB in macrophage models of infection (Helguera-Repetto et al, 2014;Sousa et al, 2015Sousa et al, , 2019. While mycobacterial burden was consistently quantified in these studies, significant differences in the times of infection and in the assays analyzed make these studies and ours complementary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, fast-growing mycobacteria, such as M. tuberculosis , destroy the cells and induce high levels of ROS. The modulation of macrophage cytokine production caused by NTM may constitute an immune-evasion strategy used to survive inside macrophages that is different from the one reported for M. tuberculosis (Helguera-Repetto, et al, 2014). …”
Section: Differences In the Host Response Against Different M Tubmentioning
confidence: 65%
“…Slow growing mycobacteria such as M. abscessus , M. fortuitum , M. celatum, and M. tuberculosis can gain entrance into human macrophages with much more efficiency than fast-growing mycobacteria (Helguera-Repetto et al, 2014). Viable, slow-growing Mycobacteria p ersist inside macrophages without causing cell damage or inducing reactive oxygen species (ROS).…”
Section: Differences In the Host Response Against Different M Tubmentioning
confidence: 99%